Mechanisms of substrate recognition by the 26S proteasome. (April 2021) - Davis, Caroline; Spaller, Brian Logan; Matouschek, Andreas
Highlights: Many types of ubiquitin modification can target proteins to the proteasome for degradation. The ubiquitin receptors of the RP individually and cooperatively function to recognize ubiquitin chains with different linkages. Disordered regions within substrates must be of appropriate length, composition, and location to allow degradation. Proteins lacking disordered regions can be prepared by various mechanisms to enable degradation by the proteasome. Abstract : The majority of regulated protein degradation in eukaryotes is accomplished by the 26S proteasome, the large proteolytic complex responsible for removing regulatory proteins and damaged proteins. Proteins are targeted to the proteasome by ubiquitination, and degradation is initiated at a disordered region within the protein. The ability of the proteasome to precisely select which proteins to break down is necessary for cellular functioning. Recent studies reveal the subtle mechanisms of substrate recognition by the proteasome – diverse ubiquitin chains can act as potent proteasome targeting signals, ubiquitin receptors function uniquely and cooperatively, and modification of initiation regions modulate degradation. Here, we summarize recent findings illuminating the nature of substrate recognition by the proteasome.